The implementation of STAD model assissted worksheets to improve students’ activities and understanding in learning biology - Sondang Rosita Indah Togatorop; Samuel Benny Dito (Universitas Islam Negeri Sumatera Utara, 2023)
This study aims to apply the Student Teams-Achievement Division (STAD) learning model assisted student worksheet to increase learning activities and understanding of concepts in biology, especially the principle of trait inheritance material. Class action research consisting of two cycles, each cycle consisting of three encounters is used in this research method. Research instruments are in the form of pre-cycle questionnaire sheets, learning outcomes evaluation sheets, student activity observation sheets, and teacher activity observation sheets. Evaluation sheet of learning outcomes to determine the improvement of understanding of concepts in the material of the principle of inheritance of traits. Student and teacher activity sheets are used to view the interactions that occur between teachers and students. Descriptive statistics are used in the analysis data to see student learning outcomes and increased student activity. The results of the study concluded that the understanding of student concepts and the increase in learning activities. The percentage of learning activities in cycle I and cycle II respectively averaged 50.95% and 81.21%. The percentage of learning outcomes in cycle I and cycle II respectively averaged 64.61% and 84.31%. The percentage of students who completed cycle I and cycle II respectively was 44.44% and 80.56%. So it can be concluded that the learning with STAD model assisted worksheets can improve students’ activities and understanding on the material of the principle of inheritance of traits.